Review of Acanthocephala (Hemiptera: Heteroptera: Coreidae) of America north of Mexico with a key to species - Mcpherson, J. E.; Packauskas, Richard J.; Sites, Robert W.; Taylor, Steven J.; Bundy, C. Scott; Bradshaw, Jeffrey D.; Mitchell, Paula Levin (Zootaxa, 2011)
A review of Acanthocephala of America north of Mexico is presented with an updated key to species. A. confraterna is considered a junior synonym of A. terminalis, thus reducing the number of known species in this region from five to four. New state and country records are presented.